2019
DOI: 10.1002/adma.201901139
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Fast Synthesis and Active Sites Deciphering of Hierarchical Foam‐Like Trimetal–Organic Framework Nanostructures as a Platform for Highly Efficient Oxygen Evolution Electrocatalysis

Abstract: Metal–organic frameworks (MOFs) have attracted tremendous interest due to their promising applications including electrocatalysis originating from their unique structural features. However, it remains a challenge to directly use MOFs for oxygen electrocatalysis because it is quite difficult to manipulate their dimension, composition, and morphology of the MOFs with abundant active sites. Here, a facile ambient temperature synthesis of unique NiCoFe‐based trimetallic MOF nanostructures with foam‐like architectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
212
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 410 publications
(222 citation statements)
references
References 70 publications
10
212
0
Order By: Relevance
“…, it only needs a small overpotential of 270 mV (RuO 2 : 277 mV). It was reported that Fe may have the positive role for OER since the doping of Fe may exert a partial-charge transfer activation effect on Co and improve the conductivity [50]. In addition, larger overpotentials of 319 mV are required to achieve the same current density for CoP, which further demonstrates that the synergetic effect of Co and Fe in the catalyst.…”
Section: Resultsmentioning
confidence: 95%
“…, it only needs a small overpotential of 270 mV (RuO 2 : 277 mV). It was reported that Fe may have the positive role for OER since the doping of Fe may exert a partial-charge transfer activation effect on Co and improve the conductivity [50]. In addition, larger overpotentials of 319 mV are required to achieve the same current density for CoP, which further demonstrates that the synergetic effect of Co and Fe in the catalyst.…”
Section: Resultsmentioning
confidence: 95%
“…Additionally, the most used approaches for preparing MOF‐derived materials is the pyrolysis process, which is energy and time‐consuming. The facile one‐step or in situ transformation of MOF into active electrocatalysts could be promising for future studies . The facile one‐step transformation or in situ transformation of MOFs could modulate the coordination environment by well controlling the parameters of compositions, structure and morphology, and substrates.…”
Section: Summary Challenges and Prospectsmentioning
confidence: 99%
“…[41] NiCoFe hierarchical foam-like MOF was synthesised in room temperature and the process only took one hour. [42]…”
Section: Conventional Methodsmentioning
confidence: 99%
“…[1,59] Qizhu et al presented the preparation of hierarchical trimetallic NiCoFe-based MOF nanostructure via a simple and scalable method at room temperature (Figure 2-12). [42] Three metal acetates were performed as metal sources with the optimised atomic ratio of Ni/Co/Fe to synthesise hierarchical foam-like morphology, which provided an appropriate platform for active components exposure. Consequently, the ultimate catalyst showed outstanding activity for OER (with the overpotential of 257 mV to reach the current density of 10 mA cm -2 ), which was contributed to favourable charge transferability and the exposing of extra active sites.…”
Section: Morphology Controlmentioning
confidence: 99%
See 1 more Smart Citation